COMPARATIVE ASSESSMENT OF GROWTH PERFORMANCE AND SURVIVAL RATE OF Oreochromis niloticus FRY REARED IN DIFFERENT COLOURS OF CULTURE MEDIUM (PLASTIC BOWLS) (FULafia Journal of Science and Technology, 2025)
This study was performed to compare the growth and survival rate of Oreochromis niloticus fry in different colours of plastic bowl (50 liters) for 10 weeks. Fry of O. niloticus (mean weight 0.08 g and body length of 0.53 cm) were stocked at 20 fish per bowl (white, red, black, green and blue bowls) in triplicates. They were fed with 45% Crude Protein Coppen feed at 5% body weight. Feeding was done twice daily, between 8 to 9 am and 4 to 5 pm. At harvest, the growth was significantly highest in black bowl but lowest survival of 52.7% (p
Keywords: Tilapia, Color, Growth performance, Plastic bowl